Polymer, preparation method thereof and cation exchange membrane

The side chain sulfonic acid polymer prepared by polyhydroxy alkylation reaction solves the shortcomings in the mechanical properties, ion separation properties and cost of the existing cation exchange membrane, and realizes a high-performance and low-cost cation exchange membrane, which is suitable for the field of electrodialysis desalination.

CN119912664AActive Publication Date: 2025-05-02UNIV OF SCI & TECH OF CHINA
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510415549.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-05-02
Estimated Expiration
2045-04-01

AI Technical Summary

Technical Problem

The existing cation exchange membranes have shortcomings in mechanical properties, ion separation properties and costs, which limit their application in the field of electrodialysis desalination.

Method used

A polymer is used whose structure is prepared by polyhydroxy alkylation reaction of 2,2-bis(3-sulfonated propoxy)biphenyl disodium, biphenyl, trifluoroacetone, 2,2'-dihydroxybiphenyl and indole-2,3-dione to form a side chain sulfonic acid-type cation exchange membrane. This method simplifies the preparation process, reduces costs, and improves the mechanical properties and ion separation properties of the membrane by regulating the relative position and content of the sulfonic acid groups.

Benefits of technology

The prepared cation exchange membrane has high cation flux, low membrane resistance, good mechanical properties and chemical stability. It is suitable for long-term electrodialysis and desalination operations, and is simple in process and low in cost, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912664A_ABST
    Figure CN119912664A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer, a preparation method thereof and a cation exchange membrane, and belongs to the technical field of ion exchange membranes. The structure of the polymer is shown as a formula 1, a formula 2 or a formula 3. Wherein m, n, x, y, a, b, c and d are polymerization degrees; m is selected from 1, 1 < = n < = 5; x is selected from 1, and y is equal to 5; 0.4 < = a < = 1, 1 < = b < = 5, c is selected from 1-a, and d is selected from 5-b. The cation exchange membrane prepared from the polymer is a homogeneous membrane, and has relatively high cation flux, relatively low membrane resistance and relatively long service life. The preparation method of the cation exchange membrane is simple in process, short in reaction period, mild in condition, simple in post-treatment and suitable for large-scale industrial production, and the production cost is remarkably reduced. # imgabs 0 # formula 1 # imgabs 1 # formula 2 # imgabs 2 # formula 3
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ion exchange membranes, and in particular to a polymer and a preparation method thereof, and a cation exchange membrane. Background Art

[0002] Electrodialysis technology is widely used in the fields of energy, chemical production, pharmaceutical purification, water treatment, etc. It uses an external electric field as a driving force to make ions migrate in a directional manner, selectively pass through the ion exchange membrane, and separate the electrolytes in the solution. Among them, the ion exchange membrane is an important membrane group component that determines the quality of electrodialysis separation performance. At present, the common commercial cation exchange membranes for electrodialysis water treatment on the market mainly include polymer membrane materials such as perfluorosulfonic acid, polysulfone, and polyether ketone. They generally have high prices, complex preparation processes, and unsatisfactory dimensional stability, mechanical strength, and ion separation performance. These problems have greatly limited their application in many important fields. Therefore, domestic and foreign researchers are urgently needed to explore the synthesis of low-cost, simple processes, industrially scalable cation exchange membranes with good mechanical properties and ion separation performance.

[0003] Cation exchange membranes are composed of polymer skeletons, negatively charged acidic active groups and positively charged counterions. They can be divided into main chain type and side chain type cation exchange membranes according to the connection mode between active groups and polymer skeletons. When negatively charged functional groups are directly linked to the main chain structural units, it is a main chain type cation exchange membrane, which is the main membrane material in the early stage of the development of homogeneous cation exchange membranes; when negatively charged functional groups are linked to the main chain structural units through spacer groups or the groups exist in the grafted chains, it is a side chain type cation exchange membrane. In contrast, the active groups of side chain type cation exchange membranes have a higher mobility, which is conducive to the aggregation of ionic groups, forming a microphase separation structure with the rigid hydrophobic main chain, and constructing mutually penetrating ion channels, which have more efficient ion transport and current conduction capabilities. This type of membrane material can also further optimize the membrane performance through a variety of modification methods such as regulating the length and distribution of the side chains and the connection mode with the main chain, and has gradually become the research and development focus in the field of ion exchange membranes in recent years.

[0004] Patent CN113522043A discloses a homogeneous cation exchange membrane of anionic surfactant, which provides negatively charged functional groups through a fatty anionic surfactant, forms a good homogeneous system with a polymer under the action of a solubilizing agent, and prepares a cation exchange membrane through degassing, constant temperature storage, scraping, drying, and shedding, which is applied to the field of electrodialysis concentration. Patent CN113426496A discloses a composite cation exchange membrane preparation process using polyvinylidene fluoride and phthalimide as precursors, preparing a blended membrane on a mesh, and then sulfonating with 4,4'-diaminobenzylbenzene-2,2'-disulfonic acid, using ion channels constructed by adjacent sulfonated ion exchange resins to achieve ion transmission, and relieving the phase separation between the ion exchange functional material and the substrate by blending a hydrophobic precursor with a binder, thereby improving the electrochemical performance of the cation exchange membrane. Patent CN108067102A discloses a cation exchange membrane that uses a microporous membrane as a supporting material, blends a comonomer, a crosslinking agent, and an initiator to fill the pores, and polymerizes at high temperature. This membrane has a semi-interpenetrating network structure, which promotes the selective transmission of ions by filling functional polymers, and uses a porous matrix to inhibit its water absorption and swelling, thereby improving the dimensional stability and mechanical properties of the membrane material, making it suitable for electrodialysis. However, this type of preparation process usually requires a large amount of organic solvents, which poses a certain toxicity risk, is complex, requires the preparation of the base membrane and polymer electrolyte in steps, and has a high operating energy consumption, which is not conducive to mass production.

[0005] At present, most cation exchange membranes have problems such as poor stability, easy damage, complicated synthesis process, and high cost, which are not conducive to industrial production and application. Therefore, it is of great significance to study and develop a side chain sulfonic acid cation exchange membrane material with good mechanical properties and ion separation performance, low cost, low energy consumption, simple preparation process, and industrial production for electrodialysis desalination. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a polymer and a preparation method thereof, and a cation exchange membrane. The cation exchange membrane prepared from the polymer has high cation flux and low membrane resistance, as well as good mechanical properties, ion separation performance and chemical stability.

[0007] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] The present invention provides a polymer, the structure of which is shown in Formula 1, Formula 2 or Formula 3:

[0009] Formula 1;

[0010] Formula 2;

[0011] Formula 3;

[0012] Among them, m, n, x, y, a, b, c, d are the degrees of polymerization;

[0013] Preferably, m is selected from 1, 1≤n≤5;

[0014] Preferably, x is selected from 1, y=5;

[0015] Preferably, 0.4≤a≤1, 1≤b≤5, c is selected from 1-a, and d is selected from 5-b.

[0016] More preferably, the m is selected from 1, 1≤n≤3;

[0017] More preferably, the x is selected from 1, y=5;

[0018] More preferably, c is selected from 1-a, d is selected from 5-b, 0.6≤a≤1, 3≤b≤5.

[0019] It is further preferred that the polymer has any of the following structures:

[0020] ,

[0021] ,

[0022] ,

[0023] ,

[0024] ,

[0025] , ,

[0026] .

[0027] The present invention also provides a method for preparing the above-mentioned polymer, comprising the following steps:

[0028] The polymer shown in Formula 1 is prepared by mixing 2,2-bis(3-sulfonated propoxy)biphenyl disodium, diphenyl and trifluoroacetone, and performing a polyhydroxyalkylation reaction under the catalysis of trifluoromethanesulfonic acid;

[0029] Alternatively, 2,2-bis(3-sulfonated propoxy)biphenyl disodium, 2,2'-dihydroxybiphenyl and indole-2,3-dione are mixed and subjected to polyhydroxyalkylation reaction under the action of trifluoroacetic acid and trifluoromethanesulfonic acid to prepare the polymer shown in formula 2;

[0030] Alternatively, 2,2-bis(3-sulfonated propoxy)biphenyl disodium, 2,2'-dihydroxybiphenyl and indole-2,3-dione are mixed and subjected to polyhydroxyalkylation reaction under the action of trifluoroacetic acid and trifluoromethanesulfonic acid to first obtain a polymer shown in formula 2, and then the polymer shown in formula 2 is mixed with sodium tert-butoxide and octanoyl chloride, and heated to react to prepare a polymer shown in formula 3.

[0031] The preparation method of Formula 1, Formula 2 or Formula 3 uses 2,2-bis(3-sulfonated propoxy)biphenyl disodium (DSOBP) as a functional monomer, biphenyl, trifluoroacetone, or 2,2'-dihydroxybiphenyl, indole-2,3-dione as a comonomer, and adopts a strategy of sulfonation first and then polymerization based on the polyalkylation reaction mechanism catalyzed by trifluoromethanesulfonic acid or the joint action of trifluoroacetic acid and trifluoromethanesulfonic acid. The functional monomer DSOBP is dissolved by trifluoromethanesulfonic acid, and trifluoromethanesulfonic acid is used as an electrophilic activating agent to catalyze the polyhydroxyalkylation reaction, so that the functional group (sulfonic acid group) is connected to the polymer main chain through a chemical bond and is not easy to fall off, thereby obtaining a side chain sulfonic acid type polymer.

[0032] The polymers represented by Formula 1, Formula 2 or Formula 3 use hydrophobic aromatic groups as the supporting skeleton, and self-assemble with hydrophilic sulfonic acid groups to form mutually penetrating ion clusters, thereby forming a microphase separation structure. In addition, the preparation method uses DSOBP as a functional monomer (its structure is shown below), which overcomes the problems of complicated steps of polymerization followed by sulfonation, high cost, and complex post-processing.

[0033] .

[0034] In addition, the preparation method also achieves precise control of the relative position and content of the sulfonic acid groups in the polymer represented by Formula 1, Formula 2 or Formula 3 by designing the structure of the sulfonated monomer in the polymer and regulating the addition ratio of the sulfonated monomer, thereby promoting the uniform dispersion of the negatively charged sulfonic acid groups on the main chain of the polymer.

[0035] Preferably, in the preparation of the polymer of Formula 1, the molar ratio of 2,2-bis(3-sulfonated propoxy)biphenyl disodium to diphenyl is 1:(1.5-3); in some specific embodiments of the present invention, it is preferably 1:1.5.

[0036] Preferably, the ratio of the sum of the moles of 2,2-bis(3-sulfonated propoxy)biphenyl disodium and biphenyl to the mole of trifluoroacetone is 1:(1.1-1.3); in some specific embodiments of the present invention, it is preferably 1:1.2.

[0037] Preferably, the usage ratio of trifluoromethanesulfonic acid to 2,2-bis(3-sulfonated propoxy)biphenyl disodium is (3.4-3.7) mL:1 mmol. In some specific embodiments of the present invention, it is preferably 3.54 mL:1 mmol.

[0038] Preferably, in the preparation of the polymer of Formula 2, the molar ratio of 2,2-bis(3-sulfonated propoxy)biphenyl disodium to 2,2'-dihydroxybiphenyl is 1:(4-6); in some specific embodiments of the present invention, it is preferably 1:5.

[0039] Preferably, the molar ratio of 2,2-bis(3-sulfonated propoxy)biphenyl disodium to indole-2,3-dione is 1:(6-7); in some specific embodiments of the present invention, it is preferably 1:6.6.

[0040] Preferably, the usage ratio of trifluoromethanesulfonic acid to 2,2-bis(3-sulfonated propoxy)biphenyl disodium is (4.4-4.6) mL:1 mmol. In some specific embodiments of the present invention, it is preferably 4.5 mL:1 mmol.

[0041] The polymer shown in Formula 2 introduces phenolic hydroxyl groups and secondary amine group active sites on the main chain, and based on the esterification reaction, the hydroxyl groups on the main chain react with alkyl acyl chloride to obtain the polymer shown in Formula 3 containing alkyl side chains. The polymer shown in Formula 3 adjusts the hydrophilicity and hydrophobicity of the polymer by introducing different amounts of alkyl side chains.

[0042] In some specific embodiments of the present invention, the main chain hydroxyl group of the polymer represented by Formula 2 reacts with octanoyl chloride under alkaline conditions to prepare the polymer represented by Formula 3.

[0043] Preferably, when preparing the polymer of formula 3, the molar ratio of the polymer of formula 2 to octanoyl chloride is 1:(1.2-2.0). In some specific embodiments of the present invention, it is preferably 1:1.2.

[0044] Preferably, in the present invention, when preparing the polymer represented by Formula 3, the temperature of the heating reaction is 75°C-85°C; more preferably 80°C.

[0045] The preparation of the polymer represented by the above formula 1 is carried out in a mixed solution of trifluoromethanesulfonic acid and dichloromethane. Preferably, 2,2-bis(3-sulfonated propoxy)biphenyl disodium and diphenyl are first dissolved in a mixed solution of trifluoromethanesulfonic acid and dichloromethane to obtain a mixed system S1, and then trifluoroacetone is dissolved in dichloromethane and the mixture of the two is added to the above mixed system S1 for polyhydroxyalkylation reaction.

[0046] The purpose of dissolving trifluoroacetone in dichloromethane is to slow down the volatilization rate of trifluoroacetone and increase the viscosity of the solution to facilitate the regulation of the dripping rate.

[0047] The polymer represented by Formula 1 is a white fibrous polymer.

[0048] The preparation of the polymer shown in the above formula 2 is carried out in a mixed solution of trifluoromethanesulfonic acid, trifluoroacetic acid and dichloromethane, wherein preferably, 2,2-bis(3-sulfonated propoxy)biphenyl disodium, 2,2'-dihydroxybiphenyl and indole-2,3-dione are first dissolved in a mixed solution of trifluoroacetic acid and dichloromethane to obtain a mixed system S2, and then trifluoromethanesulfonic acid is added to the mixed system S2 for polyhydroxyalkylation reaction. The polymer shown in the above formula 2 is a yellow fibrous polymer.

[0049] The addition of the mixture of trifluoroacetone and dichloromethane and trifluoromethanesulfonic acid is preferably performed dropwise under ice bath conditions.

[0050] The dropwise addition time is preferably 0.33-1 h. After the dropwise addition is completed, the reaction is transferred to room temperature, and the room temperature is preferably 10-30° C. The reaction time is preferably 0.25-4 h.

[0051] The preparation of the polymer shown in Formula 3 is carried out by mixing the polymer shown in Formula 2 with sodium tert-butoxide and octanoyl chloride and heating. The present invention also provides a cation exchange membrane, which is prepared by dissolving the polymer or the polymer prepared by the preparation method to obtain a membrane solution and then heating to shape it.

[0052] The functional groups (sulfonic acid groups) in the polymers represented by Formula 1, Formula 2 or Formula 3 are connected to the polymer main chain through chemical bonds and are not easily detached, so that the cation exchange membrane prepared therefrom has a long service life.

[0053] The negatively charged sulfonic acid groups in the polymer represented by Formula 1, Formula 2 or Formula 3 are uniformly dispersed on the polymer main chain, so that the cation exchange membrane prepared therefrom has a homogeneous structure, thereby making the cation exchange membrane have a higher cation flux and a lower membrane resistance.

[0054] Furthermore, the polymers shown in Formula 1, Formula 2 or Formula 3 form a hydrophilic and hydrophobic phase separation structure through segment self-assembly, thereby promoting the transmembrane ion transport of the cation exchange membrane prepared by the polymer, and achieving low swelling and high proton conductivity of the cation exchange membrane. Furthermore, the polarity difference of the polymers promotes the aggregation of negatively charged sulfonic acid groups in the membrane of the cation exchange membrane to form ion clusters and highly hydrophilic continuous hydration channels, promoting the migration of cations in aqueous solution, while hindering the passage of anions, and achieving ion selective separation of membrane materials.

[0055] In addition, based on the difference in hydration energy between different ions, the polymer represented by Formula 3 can adjust the hydrophilicity and hydrophobicity of the polymer by inserting different contents of alkyl side chains, further reducing the water content and swelling of the cation exchange membrane prepared therefrom, promoting the formation of the main side chain microphase separation structure of the membrane material, improving the ion separation performance and dimensional stability of the cation exchange membrane, and thus achieving more efficient ion separation.

[0056] In the cation exchange membrane of the present invention, the PDSB-x series cation exchange membrane is prepared from the polymer shown in Formula 1, and the SPB-x series cation exchange membrane is prepared from the polymer shown in Formula 2 or Formula 3.

[0057] The PDSB-x series and SPB-x series cation exchange membranes both use hydrophobic aromatic groups as the polymer skeleton, which ensures the stability of the cation exchange membrane structure prepared from the polymer, and makes it have good mechanical properties and chemical stability, and is suitable for long-term stable electrodialysis desalination operation.

[0058] Among them, x in the SPB-x series cation exchange membrane represents the theoretical grafting rate, that is, the percentage of hydroxyl groups grafted with alkyl side chains to all hydroxyl groups on the main chain. In Formula 3 described in the present invention, x is equal to b / (b+d).

[0059] Preferably, the cation exchange membrane has a thickness of 40-300 μm.

[0060] Preferably, in the present invention, the concentration of the polymer represented by Formula 1, Formula 2 or Formula 3 in the membrane solution is 5 wt%-10 wt%.

[0061] Preferably, the solvent of the membrane solution is selected from dimethyl sulfoxide or N,N-dimethylformamide.

[0062] Preferably, the heating and shaping temperature is 65°C-75°C.

[0063] The heating and setting time is preferably 3-6 h.

[0064] The cation exchange membrane further includes post-treatment after heating and shaping.

[0065] The post-treatment is as follows: removing the membrane after heating and setting and storing it in pure water or sodium chloride solution to obtain a cation exchange membrane.

[0066] The concentration of the sodium chloride solution is preferably 0.1 mol·L -1 .

[0067] Compared with the prior art, the polymer provided by the present invention has a structure as shown in Formula 1, Formula 2 or Formula 3; wherein m, n, x, y, a, b, c, d are the degrees of polymerization; m is selected from 1, 1≤n≤5; x is selected from 1, y=5; 0.4≤a≤1, 1≤b≤5, c is selected from 1-a, d is selected from 5-b. The cation exchange membrane prepared from the polymer is a homogeneous membrane with high cation flux, low membrane resistance and long service life. The preparation method of the cation exchange membrane has a simple process, a short reaction cycle, mild conditions, and simple post-treatment, which significantly reduces the production cost and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 The appearance diagram and internal structure schematic diagram of the cation exchange membrane described in Example 1 (Figure a), Example 5 (Figure b), and Example 6 (Figure c);

[0069] Figure 2 The PDSB-2.5 (a) and DSOBP (b) prepared in Example 3 1 H NMR spectrum;

[0070] Figure 3 are the infrared characterization results of the cation exchange membranes prepared in Examples 1-4 respectively;

[0071] Figure 4 are AFM images of cation exchange membranes PDSB-1.5, PDSB-2, PDSB-2.5, and PDSB-3 prepared in Examples 1-4, respectively;

[0072] Figure 5 This is a comparative analysis of the NaCl salt concentration limit of the membrane (PDSB-2.5) prepared in Example 3 and the commercial CM-2 membrane. Figure a is a curve showing the change of conductivity over time, and Figure b is a curve showing the change of voltage during operation.

[0073] Figure 6 is a diagram of a desalination performance test device used for the cation exchange membrane prepared in Examples 1-4;

[0074] Figure 7 The SPB-80% (a) and SPB (b) prepared in Example 7 1 H NMR spectrum;

[0075] Figure 8 are the infrared characterization results of the cation exchange membranes prepared in Examples 5-8;

[0076] Fig. 9 This is a diagram of the desalination performance test device used for the membranes prepared in Examples 5-8. DETAILED DESCRIPTION

[0077] In order to further illustrate the present invention, the polymer and its preparation method and the cation exchange membrane provided by the present invention are described in detail below with reference to the embodiments.

[0078] Example 1

[0079] The steps for preparing cation exchange membrane are as follows:

[0080] (1) Preparation of PDSB-1.5: Weigh 7.52 g of sulfonated diaryl monomer 2,2-bis(3-sulfonated propoxy)biphenyl disodium (DSOBP) into a round-bottom three-necked flask, then add 56 mL of trifluoromethanesulfonic acid and 20 mL of dichloromethane, insert an electric stirrer, stir at room temperature, and stir until dissolved. Add 3.60 g of biphenyl and continue stirring at room temperature until the solution is evenly mixed without obvious stratification. Place the three-necked flask in an ice bath, wait until the temperature stabilizes at around 0 °C, and slowly drop a mixed solution of 5.32 g of trifluoroacetone and 20 mL of dichloromethane into the three-necked flask. After the addition is complete, remove the three-necked flask from the ice bath, react at room temperature for 0.6 h, and then slowly drop the reaction solution into pure water to precipitate a white fibrous product of PDSB-1.5. Soak and rinse the product repeatedly with pure water to rinse off the acid remaining on the surface of the product. The polymer was taken out and dried to obtain polymer PDSB-1.5, whose structural formula is:

[0081] .

[0082] (2) Preparation of membrane solution: Weigh 1.00 g of polymer PDSB-1.5 into a 20 mL round-bottom flask, add 9.00 g of N,N-dimethylformamide into the flask, add a magnet, and stir on a magnetic stirrer until dissolved to obtain a membrane solution.

[0083] (3) Membrane preparation: Take 5 mL of membrane solution and pour it evenly on a glass plate. Place the glass plate on a heating table and heat treat it at 70 °C for 3 h to form a cation exchange membrane. Take out the membrane and place it on a 0.1 mol·L -1 Store in sodium chloride solution.

[0084] Example 2

[0085] The steps for preparing cation exchange membrane are as follows:

[0086] (1) Preparation of PDSB-2: The same preparation method as in Example 1 was used, except that the amounts of biphenyl and trifluoroacetone added were adjusted to 4.80 g and 6.39 g, respectively.

[0087] The structural formula of PDSB-2 is:

[0088] .

[0089] (2) Preparation of membrane liquid and membrane: The same preparation method as in Example 1 was adopted.

[0090] Example 3

[0091] The steps for preparing cation exchange membrane are as follows:

[0092] (1) Preparation of PDSB-2.5: The same preparation method as in Example 1 was used, except that the amounts of biphenyl and trifluoroacetone added were adjusted to 6.10 g and 7.45 g, respectively.

[0093] (2) Preparation of membrane liquid and membrane: The same preparation method as in Example 1 was adopted.

[0094] The structural formula of PDSB-2.5 is:

[0095] .

[0096] The membrane material prepared in Example 3 was used to conduct a salt concentration experiment to verify the actual concentration effect of the membrane material. The experimental results are as follows: Figure 5 As shown, the commercial membrane CM-2 was tested for comparison. After 100 min of electrodialysis experiment, the conductivity in the concentration chamber first increased linearly and then gradually stabilized, reaching the concentration limit, which was equivalent to the commercial membrane CM-2. The salt concentration in the desalination chamber remained almost unchanged, the resistance of the membrane stack did not change much during the electrodialysis operation, and the voltage tended to be stable. During the operation of the membrane stack, the volume of the concentration chamber gradually increased, and the growth rate of the salt concentration in the concentration chamber gradually decreased. This is because as the NaCl concentration in the concentration chamber continues to increase, the concentration difference between the concentrated and dilute chambers increases, the forward osmosis of water molecules and the reverse diffusion of ions intensify, and when the electrical migration and reverse diffusion of the target ions reach equilibrium, the salt concentration in the concentration chamber remains unchanged and reaches the concentration limit.

[0097] In addition, although PDSB-2.5 showed concentration performance comparable to that of commercial membranes in the later stage of concentration, the overall operating voltage of the membrane material prepared in Example 3 was slightly lower than that of the CM-2 membrane, which means that the membrane material prepared in Example 3 would have lower energy consumption performance during actual operation.

[0098] Example 4

[0099] The steps for preparing cation exchange membrane are as follows:

[0100] (1) Preparation of PDSB-3: The same preparation method as in Example 1 was used, except that the amounts of biphenyl and trifluoroacetone added were adjusted to 7.30 g and 8.52 g, respectively.

[0101] (2) Preparation of membrane liquid and membrane: The same preparation method as in Example 1 was adopted.

[0102] The structural formula of PDSB-3 is:

[0103] .

[0104] The membrane materials prepared in the above examples 1-4, i.e., cation exchange membranes, were respectively prepared as follows: Figure 6 The test conditions shown are at 15 mA·cm -2 The desalination performance of the membrane material was tested under the current density, and the results are shown in Table 1. At the same time, the desalination performance of the commercial membrane CM-2 was tested by the same method for comparison. In addition, the polymer PDSB-2.5 prepared in Example 3 was verified by NMR, and the results are shown in Table 1. Figure 2 In addition, the infrared spectra of the membrane materials prepared in the above examples 1-4 were tested using a Fourier transform infrared spectrometer, and the results are as follows: Figure 3 shown.

[0105] Above Figure 6 The test conditions shown are specifically:

[0106] The electrodialysis device was used at 15 mA·cm -2 At a current density of 0.1 mol·L -1 The desalination performance of the PDSB-x series (x is 1.5 or 2 or 2.5 or 3) membrane materials was evaluated by comparing the desalination rate, salt flux, device energy consumption and current efficiency with the commercial membrane CM-2 in a 25 min desalination test. Figure 6 The sodium sulfate in the electrolyte is the cathode liquid and only serves to conduct the circuit.

[0107] Example 5

[0108] The steps for preparing cation exchange membrane are as follows:

[0109] (1) Preparation of SPB: Weigh 4.74 g of sulfonated diaryl monomer 2,2-bis(3-sulfonated propoxy)biphenyl disodium (DSOBP) into a round-bottom three-necked flask, then add 45 mL of trifluoroacetic acid and 30 mL of dichloromethane, insert an electric stirrer, and stir at room temperature until dissolved. Then add 9.31 g of 2,2'-dihydroxybiphenyl and 9.72 g of indole-2,3-dione, and continue stirring at room temperature until the solution is evenly mixed without obvious stratification. Place the three-necked flask in an ice bath, wait until the temperature stabilizes at around 0 °C, slowly drop 45 mL of trifluoromethanesulfonic acid into the three-necked flask, remove the three-necked flask from the ice bath after the addition is complete, react at room temperature for 0.25 h, and slowly pour the reaction system into pure water to precipitate a light yellow fibrous product. Soak and rinse the product repeatedly with pure water to remove the acid and unreacted monomers remaining on the surface of the product. The polymer is taken out and dried to obtain polymer SPB, whose structural formula is:

[0110] .

[0111] (2) Preparation of membrane solution: Weigh 1.00 g of SPB into a 20 mL round-bottom flask, add 9.00 g of dimethyl sulfoxide into the flask, add a magnetic bar, and stir on a magnetic stirrer until dissolved to obtain a membrane solution.

[0112] (3) Membrane preparation: Take 5 mL of membrane solution and pour it evenly on a glass plate. Place the glass plate on a heating table and heat it at 65 °C for 3 h. Then, raise the temperature to 75 °C and heat it for 3 h to obtain a cation exchange membrane. Take out the membrane and place it on a 0.1 mol·L -1 Store in sodium chloride solution.

[0113] Example 6

[0114] The steps for preparing cation exchange membrane are as follows:

[0115] (1) Preparation of SPB: The same preparation method as in Example 5 was adopted.

[0116] (2) Preparation of SPB-60%: Weigh 4.55 g of SPB polymer into a round-bottom flask, add 60.45 g of dimethyl sulfoxide, insert an electric stirrer, start stirring at room temperature, stir until dissolved, add 1.57 g of sodium tert-butoxide, place the flask in a water bath, adjust the temperature to 80 °C, stir until there are no obvious solid particles, slowly drop 2.42 g of octanoyl chloride into the flask, and continue to react under 80 °C water bath conditions for 24 h. After the reaction is completed, slowly pour the reaction solution into a hydrochloric acid aqueous solution to precipitate a white fibrous product of SPB-60%. Soak and rinse the product repeatedly with pure water to remove the acid, organic reagents and unreacted monomers remaining on the surface of the product. Take out the polymer and air-dry it at room temperature to remove moisture to obtain a polymer SPB-60%, whose structural formula is:

[0117] .

[0118] (3) Preparation of membrane solution: The same preparation method as in Example 5 was adopted.

[0119] (4) Membrane preparation: Take 5 mL of membrane solution and pour it evenly on a polytetrafluoroethylene plate. Set the heating table to 65°C and heat for 4 h to obtain a cation exchange membrane. Take out the membrane and place it on a 0.1 mol·L -1 Store in sodium chloride solution.

[0120] Figure 1The figures are the appearance and internal structure schematic diagrams of the cation exchange membranes described in Example 1 (Figure a), Example 5 (Figure b), and Example 6 (Figure c). The results show that the functional monomers in the membrane material are evenly distributed on the main chain, the polymer chains form a comb-like structure, and the overall structure is regular.

[0121] Example 7

[0122] The steps for preparing cation exchange membrane are as follows:

[0123] (1) Preparation of SPB: The same preparation method as in Example 5 was adopted.

[0124] (2) Preparation of SPB-80%: The same preparation method as in Example 6 was used, except that 1.57 g of sodium tert-butoxide was replaced by 2.09 g of sodium tert-butoxide, and 2.42 g of octanoyl chloride was replaced by 3.22 g of octanoyl chloride.

[0125] (3) Preparation of membrane solution: The same preparation method as in Example 5 was adopted.

[0126] (4) Preparation of membrane: The same preparation method as in Example 6 was adopted.

[0127] The structural formula of SPB-80% is:

[0128] .

[0129] Example 8

[0130] The steps for preparing cation exchange membrane are as follows:

[0131] (1) Preparation of SPB: The same preparation method as in Example 5 was adopted.

[0132] (2) Preparation of SPB-100%: The same preparation method as in Example 6 was used, except that 1.57 g of sodium tert-butoxide was replaced by 2.62 g of sodium tert-butoxide, and 2.42 g of octanoyl chloride was replaced by 4.03 g of octanoyl chloride.

[0133] (3) Preparation of membrane solution: The same preparation method as in Example 5 was adopted.

[0134] (4) Preparation of membrane: The same preparation method as in Example 6 was adopted.

[0135] The structural formula of SPB-100% is:

[0136] .

[0137] The membrane materials prepared in the above examples 5-8, i.e., cation exchange membranes, were treated as follows: Fig. 9 The test conditions shown are at 10 mA·cm -2The desalination performance of the membrane was tested under a current density of 1.5 %. The results are shown in Table 2. The desalination performance of the commercial membrane CM-2 was tested by the same method for comparison. In addition, the infrared spectrum of the membrane materials prepared in Examples 5-8 was tested by Fourier infrared spectrometer. Figure 8 shown.

[0138] Above Fig. 9 The test conditions shown are specifically:

[0139] The electrodialysis device was used at 10 mA·cm -2 At a current density of 0.1 mol·L -1 The desalination performance of SPB and SPB-x series membrane materials was evaluated by comparing the desalination rate, salt flux, device energy consumption and current efficiency with the commercial membrane CM-2 in the desalination test of NaCl solution for 80 min. Fig. 9 The sodium sulfate in the electrolyte is the cathode liquid and only serves to conduct the circuit.

[0140] Table 1 Desalination performance test results of membrane materials prepared in Examples 1-4

[0141]

[0142] Note: The test data in Table 1 are obtained under the following conditions: the current density is 15 mA·cm -2 .

[0143] Rd (%) represents the desalination rate; J (mmol·m -2 ·s -1 ) indicates Na + Flux; EC (kWh kg -1 ) represents energy consumption; η (%) represents current efficiency.

[0144] Table 1 shows that the present invention changes the relative content of the DSOBP monomer containing sulfonic acid groups in the polymer by adjusting the content of biphenyl and trifluoroacetone, thereby changing the sulfonic acid group concentration. The membrane material (cation exchange membrane) prepared in Example 1-4 has a higher salt rejection rate and Na+ / -2-hydroxy-2-(2-hydroxy-2-pyrrolidone) when the sulfonic acid group concentration is low. + The flux and lower energy consumption and current efficiency are because the functional monomers in the membrane material of the present invention are evenly distributed on the main chain, the polymer chain forms a comb-like structure, and the overall structure is regular. In addition, due to the formation of a microphase separation structure between the rigid aromatic hydrophobic main chain (such as the benzene ring structure on the main chain) and the hydrophilic ion exchange group side chain (the side chain containing a sulfonic acid group), the construction of the ion transport membrane channel in the membrane is promoted, which is beneficial to ion transport, thereby making the desalination performance of the prepared PDSB-x series membrane materials better than that of the commercial membrane CM-2, and the electrochemical performance is good, and it has certain industrial application value.

[0145] Table 2 Desalination performance test results of membrane materials prepared in Examples 5-8

[0146]

[0147] Note: The test data in Table 2 are obtained under the following conditions: the current density is 10 mA·cm -2 .

[0148] Rd (%) represents the desalination rate; J (mmol·m -2 ·s -1 ) indicates Na + Flux; EC (kWh kg -1 ) represents energy consumption; η (%) represents current efficiency.

[0149] The results in Table 2 show that the desalination rate of SPB-x series membrane materials (Examples 6-8) increases with the increase of octanoyl chloride grafting rate, Na + The flux is positively correlated with the grafting rate of octanoyl chloride, and the current efficiency increases with the increase of the grafting rate of octanoyl chloride. This is because the hydrophobic alkyl side chain (alkyl side chain grafted by octanoyl chloride) is grafted and modified, and the water content is reduced, which further promotes the microphase separation of the membrane material, constructs ion channels, and promotes cation transport. Among them, the electrodialysis desalination performance of the SPB-100% membrane is the most outstanding, with a desalination rate of 82.44%. At the same time, it has a higher salt flux and lower energy consumption (EC=7.35 kWh·kg -1 ) and a higher current efficiency (η=88.24%), which are better than the commercial CM-2 membrane, and have good application prospects in the field of electrodialysis seawater desalination, and have certain industrial application value. + The flux is not as good as the commercial membrane CM-2, but its energy consumption and current efficiency are better than the commercial membrane CM-2. Therefore, the advantages of various aspects show that the SPB-x series cation exchange membrane prepared by the present invention has better performance than the commercial membrane CM-2.

[0150] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A polymer, characterized in that The structure is shown in Formula 1, Formula 2 or Formula 3: Formula 1; Formula 2; Formula 3; Among them, m, n, x, y, a, b, c, d are the degrees of polymerization; m is selected from 1, 1≤n≤5; x is selected from 1, y=5; 0.4≤a≤1, 1≤b≤5, c is selected from 1-a, d is selected from 5-b.

2. The polymer according to claim 1, characterized in that The m is selected from 1, 1≤n≤3; The x is selected from 1, y=5; The c is selected from 1-a, the d is selected from 5-b, 0.6≤a≤1, 3≤b≤5.

3. The polymer according to claim 1, characterized in that The polymer has any of the following structures: 、 、 、 、 、 、 、 。 4. The method for preparing a polymer according to any one of claims 1 to 3, comprising the following steps: The polymer shown in Formula 1 is prepared by mixing 2,2-bis(3-sulfonated propoxy)biphenyl disodium, diphenyl and trifluoroacetone, and performing a polyhydroxyalkylation reaction under the catalysis of trifluoromethanesulfonic acid; Alternatively, 2,2-bis(3-sulfonated propoxy)biphenyl disodium, 2,2'-dihydroxybiphenyl and indole-2,3-dione are mixed and subjected to polyhydroxyalkylation reaction under the action of trifluoroacetic acid and trifluoromethanesulfonic acid to prepare the polymer shown in formula 2; Alternatively, 2,2-bis(3-sulfonated propoxy)biphenyl disodium, 2,2'-dihydroxybiphenyl and indole-2,3-dione are mixed and subjected to polyhydroxyalkylation reaction under the action of trifluoroacetic acid and trifluoromethanesulfonic acid to first obtain a polymer shown in formula 2, and then the polymer shown in formula 2 is mixed with sodium tert-butoxide and octanoyl chloride, and heated to react to prepare a polymer shown in formula 3.

5. The preparation method according to claim 4, characterized in that: When preparing the polymer shown in Formula 1, the molar ratio of 2,2-bis(3-sulfonated propoxy)biphenyl disodium to diphenyl is 1:(1.5-3); The ratio of the sum of the moles of 2,2-bis(3-sulfonated propoxy)biphenyl disodium and biphenyl to the mole of trifluoroacetone is 1:(1.1-1.3); The dosage ratio of trifluoromethanesulfonic acid and 2,2-bis(3-sulfonated propoxy)biphenyl disodium is (3.4-3.7) mL: 1 mmol; When preparing the polymer shown in formula 2, the molar ratio of 2,2-bis(3-sulfonated propoxy)biphenyl disodium and 2,2'-dihydroxybiphenyl is 1:(4-6); The molar ratio of 2,2-bis(3-sulfonated propoxy)biphenyl disodium to indole-2,3-dione is 1:(6-7); The dosage ratio of trifluoromethanesulfonic acid and 2,2-bis(3-sulfonated propoxy)biphenyl disodium is (4.4-4.6) mL: 1 mmol; When preparing the polymer shown in formula 3, the molar ratio of the polymer shown in formula 2 to octanoyl chloride is 1:(1.2-2).

6. The preparation method according to claim 4, characterized in that: When preparing the polymer represented by formula 3, the temperature of the heating reaction is 75°C-85°C.

7. A cation exchange membrane, characterized in that: The film liquid is obtained by dissolving the polymer described in any one of claims 1 to 3 or the polymer prepared by the preparation method described in any one of claims 4 to 6, and then heating and shaping.

8. The cation exchange membrane according to claim 7, characterized in that The thickness of the cation exchange membrane is 40-300 μm.

9. The cation exchange membrane according to claim 7, characterized in that The concentration of the polymer represented by Formula 1, Formula 2 or Formula 3 in the membrane solution is 5 wt%-10 wt%.

10. The cation exchange membrane according to claim 7, characterized in that: The solvent of the membrane solution is selected from dimethyl sulfoxide or N,N-dimethylformamide; The temperature of the heating and setting is 65°C-75°C.

Citation Information

Patent Citations

  • Cation exchange membrane and preparation method thereof

    CN108067102A

  • Preparation method of composite cation exchange membrane

    CN113426496A

  • Preparation method and application of homogeneous cation exchange membrane of anionic surfactant

    CN113522043A

  • Proton exchange membrane with polymer main chain of aromatic ring structure and preparation method thereof

    CN113150344A

  • Hydrophilic and hydrophobic rigid large-volume co-regulated anion exchange membrane and preparation method thereof

    CN113782761A